Diurnal heat exposure risk mapping and related governance zoning: A case study of Beijing, China. (June 2022) - Chen, Bin; Xie, Miaomiao; Feng, Qianqian; Wu, Rongrong; Jiang, Lei
Highlights: Diurnal heat exposure risk assessment was conducted. There were differences in the spatial distribution of daytime and nighttime risks. High-risk patterns at night were similar to population distribution. Local climate zone is a reasonable heat exposure risk governance unit. The governance zoning applicable to heat exposure risk governance was proposed. Abstract: Heat exposure risk mapping and governance are necessary due to the negative impact of urban heat hazards on residents' health. Heat exposure risk is dynamic in time and space due to diurnal temperature variations and population mobility, but has often been ignored in previous studies. This study assessed diurnal heat exposure risk by coupling high-temperature intensity and frequency and population density in Beijing, China, and proposed risk governance zoning based on the association analysis of local climate zone (LCZ) and heat exposure risk. The results indicate that although heat exposure risk is highest in the core functional area during the day and night, the gravity centre of heat exposure risk shifts eastward at night; high-risk patterns at night are similar to the population distribution. Moreover, based on the different LCZs contributing differently to high heat exposure risk, risk governance zoning that is applicable to heat exposure risk governance was developed; urgent priority governance areas account for 22.88% of the total area due to a large number of compact mid-rise and high-rise buildings. These findings could represent an important basis for developing risk mitigation strategies in urban planning, and provide effective guidance for urban residents to improve their risk adaptation capacity.